2017
DOI: 10.29086/2519-5476/2017/v24n2a8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Cognitive Demand in Higher Education Account i ng Textbooks

Abstract: Driven by requirements prescribed by professional bodies, the accounting curriculum in many higher education institutions in South Africa and Nigeria demands high cognitive attributes from graduates. Advancing the proposition that assessment drives learning, the authors contend that cognitive demand can be determined by analysing the assessment tasks in students' textbooks. Using a conceptual framework based on Bloom's revised taxonomy and levels of difficulty theory, this article analyses the cognitive demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In both textbooks, the content is sequenced and paced in such a way as to assist the teacher with planning and teaching. This was also evident in the assessment tasks that were based on the hierarchy of knowledge and skills as they are influenced by the sequence of topics (Arek-Bawa & Dhunpath 2017). By providing in-text assessments along with the concepts under each sub-topic, both textbooks facilitated ease of comprehension (Sunday 2014;Widodo 2007).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In both textbooks, the content is sequenced and paced in such a way as to assist the teacher with planning and teaching. This was also evident in the assessment tasks that were based on the hierarchy of knowledge and skills as they are influenced by the sequence of topics (Arek-Bawa & Dhunpath 2017). By providing in-text assessments along with the concepts under each sub-topic, both textbooks facilitated ease of comprehension (Sunday 2014;Widodo 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Accounting contains many unique terms and abstract knowledge which are exclusive to the discipline. Understanding these terms and concepts is regarded as the principal skill which serves as a foundation for application and analytical and evaluation skills in each accounting topic (Arek-Bawa & Dhunpath 2017;DBE 2011;DoE 2008). Learners should be acquainted with these unique terms and concepts to communicate and solve problems within the discipline (Ngwenya 2012;Stephenson 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Accounting curriculum emphasises conceptual coherence, sequence and progression of knowledge in a manner that assists the teachers with planning and teaching and to facilitate ease of comprehension (Arek-Bawa & Dhunpath, 2017;Bharath, 2015;DBE, 2011). However, in this study teachers indicated that textbooks were misleading in terms of helping teachers in structuring teaching in a logical order.…”
Section: Discussionmentioning
confidence: 99%
“…While there is substantial literature on textbooks internationally (Cho, 2017;Morales & Baker, 2018;Liang & Cobern, 2013;Lin & Yang, 2015;Sunday, 2014;Tarmana & Kuran, 2015;Yang & Sianturi 2017), few studies have been embarked on textbooks in South Africa (Arek-Bawa & Dhunpath, 2017;Bargate, 2012;Bharath, 2015;Chirwa & Naidoo, 2016). Furthermore, literature shows that there is a shortage of research on the quality of Accounting textbooks.…”
Section: Introductionmentioning
confidence: 99%